Gastric cancer in children and adolescents in Japan. Issue 1 (14th January 2019) - Okuda, Masumi; Nomura, Keiko; Kato, Mototsugu; Lin, Yingsong; Mabe, Katsuhiro; Miyamoto, Ryosuke; Okumura, Akihisa; Kikuchi, Shogo
Abstract: Background: Very limited data are available on childhood gastric cancer. Using a retrospective survey and literature review, we assessed the clinical features of gastric cancer in children and adolescents. Methods: We collected information on childhood gastric cancer from pediatricians of 518 hospitals that issue the title of "certified board pediatrician" approved by Japan Pediatric Society, using a questionnaire on background, diagnosis year, onset symptoms, tumor location, histology, nodular gastritis, Helicobacter pylori testing, treatment, and prognosis. Studies were collected using PubMed and the NPO Japan Medical Abstracts Society database. Data for childhood gastric cancer were abstracted from the Japanese Vital Statistics database. Results: Of the 518 hospitals, 349 returned the questionnaire, which identified four patients. Literature review identified 77 cases of gastric cancer, and we analyzed data for 80 children <16 years old. Most patients were >10 years old, and there were no sex differences. Onset symptoms ranged from abdominal pain to non‐localized. Sixteen of 44 children had a family history of cancer; 10 had a family history of gastric cancer. Histologically, approximately 80% had undifferentiated‐type carcinoma. Prognosis was extremely poor, and two of three tested children were positive for H. pylori infection. Childhood gastric cancer death has been declining. Conclusions: Childhood gastric cancer is rare in Japan, and information on H. pylori in childhood gastric cancer patients is limited. Declining childhood gastric cancer rates may reflect the decreasing prevalence of infection but further study is necessary to clarify the relationship between H. pylori and gastric cancer.